Mechanisms of large actuation strain in dielectric elastomers - Koh, Soo Jin Adrian; Li, Tiefeng; Zhou, Jinxiong; Zhao, Xuanhe; Hong, Wei; Zhu, Jian; Suo, Zhigang (Journal of polymer science. Part B, Polymer physics, 2011)
Subject to a voltage, a dielectric elastomer (DE) deforms. Voltage-induced strains of above 100% have been observed when DEs are prestretched, and for DEs of certain network structures. Understanding mechanisms of large actuation strains is an active area of research. We propose that the voltage-stretch response of DEs may be modified by prestretch, or by using polymers with “short” chains. This modification results in suppression or elimination of electromechanical instability, leading to large actuation strains. We propose a method to select and design a DE, such that the actuation strain is maximized. The theoretical predictions agree well with existing experimental data. The theory may contribute to the development of DEs with exceptional performance.